Unstationary thermal analysis of the vertical heat ground exchanger within unsaturated soils - Sławiński, Daniel (Instal, 2019)
The efficiency of heat exchange in ground heat exchangers (GHE) in many projects decreases throughout their service life. Large temperature fluctuations were observed during feeding of the exchanger and during its natural cooling. This problem stems mainly from the lack of in-depth studies on the impact of heating and humidity migration on the operation of ground heat exchanger in unsaturated soil. In our work we applied a numerical model of a porous medium with multi-component fluid flow. The mathematical description was expanded with additional streams describing the exchange of thermal energy in the backfill material and the structure of the porous model. Ground porosity was mapped geometrically and mathematically. We introduced the definition of total temperature. The results were compared with the simulations performed for the model solving the classic heat exchange equation. The model was verified on the measurement data read for 3 sensors installed at different depths of one hole and at different time intervals. The parameters of the model are based on local climatic conditions of Jabłonna near Warsaw. 24-hour operation of a single hole has been numerically mapped. The results proved a much greater convergence with the actual data than those obtained for the classic model describing heat exchange. The critical point of the model was the selection of coefficients describing the flow resistance of i-components in the porous medium and the individual components of the adopted definition of the total temperature. Extended discussions were carried out in the section on model verification. We also performed a review of works on similar topics published recently.